Hammond Atlas of World Religions : A Visual History of Our Great Faiths - Hammond World Atlas; Editorial Director; Murray, Aaron R. (Long Island City Hammond World Atlas Corp., 2009)
An illustrated survey of religions from around the world that highlights religious customs, basic beliefs, history, and key figures and prophets
Include Color Illustration, Glossary and Index
Keywords: Religions